IMPLEMENTASI KEBIJAKAN KAWASAN TANPA ROKOK STUDI KASUS STASIUN TAWANG (PERDA KOTA SEMARANG NO. 3 TAHUN 2013) - Saragih, Juniaman Alexander; Hidayat, Zainal (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Smoking is bad for human health , so as to hinder development in the health sector. This became the basis the regional government of Semarang city to make a policy governing concerning Limited Smoking Area As stated in the regulation of Semarang no. 3 year 2013. The purpose of this research is to know and to analyze the implementation of the regulation of Semarang no. 3 year 2013. To discuss concerning Limited Smoking Area regulation as well as the factors that influence on the based on the monitoring regulation of Semarang no. 3 year 2013. The method used in this research are deskriptive is a procedure to provide the data or information about m a qualitative studies, data obtained from the interview observation, and archive institute.Research results that are relevant to the problem via reduksi m a qualitative analysis, surveyed the data in accordance with the basic research and mengkerucut to focus on the main issues on the answer to this. The research results show that in the implementation regulations the implementation of this policy is considered to be quite successful however still less than optimal nevertheless there are some positive change that is felt by officials in station good tawang itself and by passengers who are at the station tawang Based the research result, There are obstacles that found supposed to be repaired as soon as possible , found a supporter of the implementation of has to be defended .Clarification on the city Semarang establishment of regulation concerning the region Limited Smoking Area as well as from the notification conducted through the media need to maintained if needs to be improved